GREEN BANKING PERFORMACE ANALYSIS: A COMPREHENSIVE REVIEW OF CIMB NIAGA’S ENVIRONMENTAL INITIATIVES - Yang, Amanda; Lukman, Hendro (International Journal of Application on Economics and Business, 2024)
Indonesia is known for being one of the countries that are at high risk of experiencing bad things like natural disasters because of climate change. One of the Indonesia government's initiatives in addressing this issue is to participate in the Paris Agreement, which implies the implementation of a green accounting system. The Implementing green accounting offers many benefits to organizations. At the same time, company management strongly embraces the idea of sustainability in their operations and chooses to disclose the social and economic impacts of their activities. In various sectors, including the banking industry, there is a growing emphasis on implementing green practices within their operations as part of an effort to enhance business ethics, called green banking. This research aims to analyze the development of CIMB Niaga's success in environmental management over the last six years. This study concentrates on developing sustainability implementation guidelines for financial institutions to implement green banking. The research methodology used in this research is quantitative, with two approaches, namely a qualitative perspective or paradigm. The data used consists of secondary data obtained from continuous reporting for the period 2016 to 2022. The results of this research are CIMB Niaga's implementation of green banking policies has been quite successful. These results provide recommendations for CIMB Niaga management to continue to improve the company's environmental performance. Improving the company's environmental performance shows management's commitment to carrying out CIMB Niaga activities based on the concept of sustainability.